REPRODUCTIVE PERFORMANCE OF WILD CAUGHT BANANA SHRIMP FENNEROPENAEUS MERGUIENSIS (DE MAN) FEMALES FROM DIFFERENT GEOGRAPHIC REGIONS OF INDIA - WAIKHOM, GUSHEINZED; PILLAI, S. M. (Journal of the Inland Fisheries Society of India, 2021)
Shrimp farming traces its origin to Southeast Asia where, for centuries, farmers have raised crops of wild shrimps in tidal fish ponds (Rosenberry, 1994). About 85 species of shrimps are known to exist in Indian waters, of which 55 species are commercially important.